2016
DOI: 10.1111/jog.12886
|View full text |Cite
|
Sign up to set email alerts
|

Successful angioplasty during pregnancy for renal artery stenosis

Abstract: Renal artery stenosis can be diagnosed during pregnancy and treated at the same time. A 30-year-old woman had a sudden, severe but asymptomatic hypertensive crisis at 21 weeks of gestation. The diagnosis of renal artery stenosis suspected on Doppler ultrasonography was confirmed and treated by renal angioplasty, which reduced her blood pressure. At 27 weeks of gestation, her blood pressure increased again, associated with significant proteinuria, suggesting pre-eclampsia. A cesarean section was performed givin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In terms of invasive treatment, percutaneous transluminal renal angioplasty with or without stenting has become the standard versus surgical revascularization. Although a recent systematic review showed only marginal benefit to this approach compared to medical therapy alone, there is evidence that select patient do have significant benefits in blood pressure control [2,8,9]. Furthermore, studies have shown that usually at least 80% stenosis is required to produce any significant hemodynamic stimulus to the renin-angiotensin system and thus may be a threshold for invasive treatment [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of invasive treatment, percutaneous transluminal renal angioplasty with or without stenting has become the standard versus surgical revascularization. Although a recent systematic review showed only marginal benefit to this approach compared to medical therapy alone, there is evidence that select patient do have significant benefits in blood pressure control [2,8,9]. Furthermore, studies have shown that usually at least 80% stenosis is required to produce any significant hemodynamic stimulus to the renin-angiotensin system and thus may be a threshold for invasive treatment [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…When possible, expedited delivery is beneficial. However, there has been some success with interventional treatment prior to delivery [2]. The high mortality risk of eclampsia continues into the the postpartum period and it is uncertain when blood pressures can be expected to normalize in preeclampsia even in the absence of renovascular hypertension [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation